Lighting Factor Analysis to Reduce Employee Eye Fatigue Using an Ergonomic Approach - Majid, Nurul Janatim; Sokhibi, Akh.; Tauhida, Dina (Universitas Ahmad Dahlan, 2022)
PT Semen Gresik is a company that produces cement with various units, one of which is a production plan and control unit whose job is to plan and evaluate work processes. The problem that exists in the production plan and control office space is the intensity of the lighting in the office space is not under the SNI Lighting standard. 16-7062 2004 for an office space of 350 lux. This can cause eye fatigue which can affect the condition of employees at work. Measurement of eye fatigue using the Visual Fatigue Index (VFI) questionnaire. The subjects of this study were all employees of the production plan and control work unit of PT Semen Gresik. The results of the measurement of eye fatigue are 4 out of 5 employees who experience eye fatigue, and the results of the calculation of the need for lamps require 8 lamps with 36 watts of power and white/daylight color temperature to achieve room lighting standards.